Beyond paternalism: pluralising Copperbelt histories - Pesa, I; Henriet, B (James Currey, 2021)
The first comparative historical analysis - local, national and transnational - of the cross-border Central African copperbelt; a key work in studies of labour, urbanisation and African studies.